Hypomagnesemia-Induced Cerebellar Syndrome—A Distinct Disease Entity? Case Report and Literature Review - Kamm, Christian P.; Nyffeler, Thomas; Henzen, Christoph; Fischli, Stefan (Frontiers in Neurology, 2020)
Clinical consequences of hypomagnesaemia are manifold and include various neurological syndromes up to life-threatening conditions. Despite its importance, magnesium is generally not routinely determined leading to an under recognition of hypomagnesaemia related disorders. In the past years, there are growing numbers of reports of hypomagnesaemia induced cerebellar syndromes (HiCS) with corresponding cerebellar oedema, which might be a distinct disease entity. To provide further insights into HiCS, we describe a patient with HiCS and performed a literature review on cerebellar syndromes due to severe hypomagnesaemia with regard to the clinical, magnetic resonance imaging (MRI) and laboratory findings. We identified 17 cases, so including our case, 18 cases contribute to this review. Summarized, HiCS seems to be a distinct disease entity due to the remarkable similarities of clinical, MRI and laboratory features. It should be diagnosed and treated early to avoid recurrent disease courses, residual symptoms and potentially life-threatening conditions such as seizures. Physicians must be alert to HiCS as magnesium is usually not part of the routine electrolyte panel.